Frakcionácia, špeciačná analýza a stanovenie tália v environmentálnych vzorkách - Kališ, Milan; Matúš, Peter; Bujdoš, Marek; Medveď, Ján (Chemické listy, 2007)
The natural sources of Tl are less bioavailable and hence of less concern in regulation than its anthropogenic sources. Tl is more toxic to mammals than Hg. Cd, Pb, Ag, Cu or Zn and has been responsible for many poisonings. Tl occurs in two oxidation states, Tl(I) and Tl(III), the former being the predominant species in natural environment. In contrast to inorganic compounds, in which the Tl(I) ion is more stable in aqueous solutions than the Tl (III) ion, the latter is more stable in organic compounds. As the Tl concentrations in environmental samples are in the µg kg-1 range or less, it is necessary to use separation and preconcentration techniques, such as coprecipitation. The frequently used methods of Tl fractionation and speciation analysis are extraction, ion exchange and ion chromatography. They are combined with Tl determination using voltammetry, neutron activation analysis, spectrophotometry, mass spectrometry, inductively coupled plasma optical emission spectrometry and electrothermal and hydride-generation AAS.
Keywords: finanční podpora výzkumu jako téma; hmotnostní spektrometrie; Research Support as Topic; Environmental Monitoring; Mass Spectrometry; thallium; Thallium; monitorování životního prostředí